2012
DOI: 10.1021/ct300132e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon/Water Interactions: Encouraging Energetics and Structures from DFT but Disconcerting Discrepancies for Hessian Indices

Abstract: In this work, ab initio electronic structure computations have been used to systematically examine the structures and energetics of nine small hydrocarbon molecules interacting with water. Full geometry optimizations and harmonic vibrational frequency calculations were performed on 30 unique dimer configurations with the MP2 method and a triple-ζ correlation consistent basis set (cc-pVTZ for H and aug-cc-pVTZ for C and O, denoted haTZ). Three different estimates of the CCSD(T) complete basis set (CBS) limit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 95 publications
5
26
0
Order By: Relevance
“…Accordingly, dispersion-corrected DFT is able to accurately describe the mono-hydrated complex. This feature is in line with other studies on hydrated species [34,45]. The LC-ωPBE-GD3BJ/Pop2, that simultaneously reproduces the selected geometric, energetic and spectroscopic features with errors less than 5%, as well as the MP2/aVDZ levels, were selected for the study of larger hydrated complexes.…”
Section: Methods Calibrationsupporting
confidence: 69%
See 1 more Smart Citation
“…Accordingly, dispersion-corrected DFT is able to accurately describe the mono-hydrated complex. This feature is in line with other studies on hydrated species [34,45]. The LC-ωPBE-GD3BJ/Pop2, that simultaneously reproduces the selected geometric, energetic and spectroscopic features with errors less than 5%, as well as the MP2/aVDZ levels, were selected for the study of larger hydrated complexes.…”
Section: Methods Calibrationsupporting
confidence: 69%
“…It was shown that dispersion-corrected density functionals may suitably describe such complexes provided that a calibration step is carried out, either with respect to the experimental data or to the results coming from high-level theoretical calculations [14,16,34].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of water-methane interactions, we have shown [8] that the repulsive wall of the pairwise interaction potential directs the OH bond of water into the threefold hollow of the methyl group, thereby facilitating closest approach of the molecules. Other studies support this conclusion [9,10,11,12]. Extending this picture to higher hydrocarbons is a goal of our ongoing work, and this letter continues that effort.…”
Section: Introductionsupporting
confidence: 52%
“…The latter six data-sets contain non-covalent (NC) interactions, which are evaluated using the aug-cc-pVTZ basis, except for the X40 data, which used the def2-TZVPPD basis set. The TC data-sets are (1) non-multi-reference total atomisation energies (TAE) [74], (2) atomisation energies of n = 1-8 alkanes (Alk19) [75], (3) diverse barrier heights (DBH24) [76][77][78], (4) adiabatic ionisation potentials (G21IP) [79,80], (5) weak hydrocarbon-water interactions (HW30) [81], (6) hydrogen-bonded and dispersion-bonded complexes (S22) [82,83], (7) interaction energies of relevant biomolecular structures (S66) [84,85], (8) small non-covalent complexes (A24) [86], (9) non-covalent interactions of halogenated molecules (X40) [87], and (10) interactions of complexes containing divalent sulphur (DS14) [88]. The final two columns give the overall RMS errors for the four TC data-sets and six NC data-sets.…”
Section: Density Functional Theory Functionalsmentioning
confidence: 99%